An Analysis of Students’ Difficulties in Pronouncing English Fricative Consonant at the Eleventh Grade of SMA Negeri 1 Kota Jambi - Ratisa Adhani; Yanti Ismiyati; Efa Silfia (Universitas Batanghari Jambi, 2021)
This research was aimed to find out the students’ difficulties and factor causes students difficult to pronounce English fricative consonant at the Eleventh Grade of SMA Negeri 1 Kota Jambi. The research methodology of this study was quantitative descriptive research which involved population and sample. The total population of this research was the XI MIPA 1 students of SMAN 1 Kota Jambi, which consisted of 36 students. In collecting the data, the researcher gave test and interview at the class. The result of the research showed that the eleventh grade students of SMA Negeri 1 Kota Jambi got difficulties in pronouncing English fricative consonant sounds of dental and labiodental. The students’ difficulties in pronouncing fricative consonant are producing sound (/q/, /ð/, and /v/). The highest percentage of the students score was 95% and the lowest was 15%. Where the mean score of the students’ test was 42,28% with a fair categories and percentage of students score test were /θ/ 76,11%, sound /ð/ 77,78%, /f/ 5%, and sound /v/ 57,22%. The factors of students’ difficulties in pronouncing English fricative consonant are; the influence of students’ mother language, the lack of students’ knowledge about English sound system and the unsuccessful in using borrowed English words.Key Words: Students Difficulties, Pronouncing, Fricative Consonant.